Determination and evaluation of biogas and methane productions of vegetable and fruit wastes with Hohenheim Batch Test method - Aybek, Ali; Üçok, Serdar (International Journal of Agricultural and Biological Engineering, 2017)
Nowadays, biogas technology applications are gradually increasing worldwide due to the economic and environmental benefits. Many researches and studies related to the determination of the biogas potential of organic waste materials have been carried out in the recent years. Studies to determine the specific methane potential of organic waste materials have a great importance for both design and economical operation of the biogas plants. Energy potential that will be recovered from organic wastes is substantial in Turkey. Thanks to biogas plants gathering vegetable-fruit wastes and other organic wastes are planned to produce significant amount of renewable energy in Turkish markets. Owing to the use of organic wastes, the disposal of waste as well as energy production, soil, water and air pollution in terms of environmental protection are also minimized. On the other hand, the organic wastes produced from plants can also be utilized as fertilizer in vegetable production. In this study, the cumulative biogas and methane production of vegetable and fruit wastes were experimentally determined with HBT (Hohenheim Batch Test) method. Biogas and methane yields of vegetable and fruit wastes were found as 0.54-0.73 Nm3/(kg ODM) and 0.29-0.37 Nm3/(kg ODM), respectively. The highest value of the cumulative specific methane production was tomato wastes (0.37 Nm3/(kg ODM)), and the lowest value was lettuce wastes (0.29 Nm3/(kg ODM)), as well. The average cumulative specific methane production values of mixed vegetable and fruit wastes are determined as 0.34 Nm3/(kg ODM). Keywords: biogas, methane production, Hohenheim Batch Test, vegetable and fruit wastes, renewable energy, Turkey DOI: 10.25165/j.ijabe.20171004.2864 Citation: Aybek A,Üçok S. Determination and evaluation of biogas and methane productions of vegetable and fruit wastes with Hohenheim Batch Test method Int J Agric & Biol Eng, 2017; 10(4): 207–215.